2003
DOI: 10.1007/s00330-002-1816-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and diagnostic value of preoperative MR mammography and FDG-PET in suspicious breast lesions

Abstract: Dynamic enhanced magnetic resonance (MR) mammography and fluorine-18 fluorodeoxyglucose positron emission tomography (FDG-PET) of the breast were directly compared preoperatively in suspicious breast lesions. Forty-two breast lesions in 40 patients were examined with a three-dimensional dynamic MR imaging series and FDG-PET. The MR and PET examinations were evaluated separately and the results were compared with the histological findings. The sensitivity and specificity of each method were calculated. The diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 24 publications
0
29
1
2
Order By: Relevance
“…21 Walter et al agree, but suggest MR mammography first and PET if differentiation of benign vs. malignant is needed, to avoid the high costs of both of these examinations. 22 Evaluation of a larger patient population with prospective studies, with the addition of mammography and breast ultrasound is needed to further determine the precise role and timing of each imaging modality in breast cancer evaluation. Availability of dedicated breast PET units with improved spatial resolution will improve breast cancer detection and their role will need to be ascertained.…”
Section: Discussionmentioning
confidence: 99%
“…21 Walter et al agree, but suggest MR mammography first and PET if differentiation of benign vs. malignant is needed, to avoid the high costs of both of these examinations. 22 Evaluation of a larger patient population with prospective studies, with the addition of mammography and breast ultrasound is needed to further determine the precise role and timing of each imaging modality in breast cancer evaluation. Availability of dedicated breast PET units with improved spatial resolution will improve breast cancer detection and their role will need to be ascertained.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that FDG PET may yield false-negative results following chemotherapy, which is mainly due to chemotherapy-induced changes in tumor metabolism. False negative results yielded by FDG PET were also reported for ductal carcinoma in situ, dependent of the tumor size, whereas falsepositive results were seen in cases of inflammation and fibrous dysplasia [122].…”
Section: M Tc-sestamibi Scintimammography In Detecting Breast Cancermentioning
confidence: 92%
“…Generally, MR imaging showed higher sensitivity, and PET showed higher specificity in the detection of axillary nodal disease. This is due to the lower spatial resolution of PET, and the missed foci were correspondingly below 15 mm in size [27]. While there seems to be consensus that FDG-PET alone is not yet sensitive enough to allow the avoidance of axillary node dissection (AND) in negative studies [28], potentially the combination of sentinel node biopsy with FDG-PET may prove to have enough sensitivity for this purpose.…”
Section: Axillary Node Stagingmentioning
confidence: 99%